PHASE II STUDY OF GEMCITABINE AND CISPLATIN IN ADVANCED NON-SMALL CELL LUNG CANCER - M. Hoseinzadeh Mollayosefy (Acta Medica Iranica, 2006)
Cisplatin-based chemotherapy is the standard treatment for advanced non-small cell lung cancer (NSCLC). Many novel drugs have been used in combination with cisplatin in this setting. Of these drugs, gemcitabine is reported to have a high response rate and acceptable toxicity. The aim of this study was to evaluate the efficacy and safety of gemcitabine and cisplatin combination. Twentythree patients with NSCLC were enrolled from January 2001 till September 2003. All of them were confirmed by histology and were in advanced stage, i.e. stage IIIB or stage IV. Cisplatin with the dose of 70 mg/m2 was given every 21 days, in combination with gemcitabine at a dose of 1250 mg/m2 administered on days 1, 8 of a 21-day cycle. Of the 23 patients, 1 showed complete remission, 5 achieved partial remission and 7 had stable disease and 2 patients showed progressive disease, 8 patients were not evaluable for response. The overall response in 15 evaluable patients was 40% (95% CI.), median survival was 13.5 months (95% CI, 3.5-27.4 months), and median progression free survival was 11 months (95% CI, 1.04-20.9 months). Hematological toxicity’s included anemia, neutropenia and thrombocytopenia. Non-hematological toxicities included nausea/vomiting, peripheral neuropathy, skin rashes, mild renal impairment and one case of acute respiratory distress syndrome;another case developed transient acute psychosis. The regimen of combined gemcitabine with cisplatin is safe and effective and well tolerated in patients. In this combination, a lower dose of cisplatin seems to have an efficacy similar to that seen in previous reports.